THE EFFECT OF BALANCED SCORECARD ON PSYCHOLOGICAL EMPOWERMENT AND MANAGERIAL PERFORMANCE IN MALAYSIAN HOTEL SECTOR - Abdul Razak, Shazrul Ekhmar; Mustapha, Mazlina; Abu Kasim, Nor Aziah (Journal of Technology Management and Business, 2016)
In current competitive business environment where basic service facilities are homogenous, hotels must adapt themselves and find way to improve their performance. For hotels, their performance depends on how they deliver service to create value to customers. Hence, hotels need to emphasize on performance of employees, especially the operation managers, because their performance in delivering service quality is vital to determine the level of customers’ satisfaction. Prior study has found that the use of Balanced Scorecard (BSC) is positively related to managers’ performance. However, it is unclear whether the use of BSC could improve managers’ performance in hotel sector. This study intends to provide useful insights by examining the effect of the use of BSC and performance of hotel managers in Malaysia hotel sector. It is also proposed that the effect of the use of BSC on manager’s performance is indirectly through mediating variable of psychological empowerment. Data were collected from a survey of 133 managers in 3, 4, and 5-star hotels in Malaysia. Results from Structural Equation Model (SEM) indicate that the use of BSC significantly influences managerial performance through mediating effect of psychological empowerment. In particular, the results highlight that the use of BSC influence manager’s psychological empowerment, which in turn, influence managerial performance.